NONPARAMETRIC TRUNCATED SPLINE REGRESSION MODELING ON POVERTY RATES IN NORTH SUMATRA - Zebua, Hasrat Ifolala (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to investigate the relationship between the Human Development Index (HDI) and poverty levels in North Sumatra. Using data from Central Bureau of Statistics (BPS), the study employs a nonparametric truncated spline regression model to analyze the relationship. The findings reveal that HDI significantly impacts poverty levels, with higher HDI associated with lower poverty rates. The model used in this study offers a robust approach to understanding the dynamics between HDI and poverty, and the results underscore the importance of improving HDI to reduce poverty. The research highlights an R-Squared value of 82.35%, indicating a strong correlation between HDI and poverty in the region.